PEMILIHAN METODE DAN MODEL PEMBELAJARAN BAHASA INDONESIA BERDASARKAN TUNTUTAN KURIKULUM 2013 (KAJIAN KONSEPTUAL PEMBELAJARAN BAHASA INDONESIA DI SMA) - Mas’ud, Lalu (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2014)
The present study was library research aimed at finding out and conceptually considering Indonesian language learning models that are relevant to the contents demanded in 2013 Curriculum and its classroom implementation principles. The study results concluded that effective learning of Indonesian language as demanded by 2013 Curriculum must develop two modes of learning process, i.e. indirect learning process and direct learning process. The two modes of learning process must be implemented integratedly. To attain effectiveness of genre-based Indonesian learning with scientific approach, needed are learning methods and models that can accommodate the implementability of the approach in the learning process. Learning methods and models that are considered as being able to accommodate the scientific steps in the learning process as demanded by 2013 Curriculum are Discovery-Based Learning, Project-Based Learning, and Problem-Based Learning. Related to the learning models, Indonesian language instruction with scientific approach begins with the preparation of lesson plan developed by teachers either individually or in group by referring to the syllabus and course book. In this case, the three models are seen as being very effective in supporting the attaintment of all competencies contained in 2013 Curriculum integratedly.Key words: learning models, 2013 Curriculum